Beneficial Effects of GH in Young Adults With Prader-Willi Syndrome: A 2-Year Crossover Trial - Kuppens, Renske J; Bakker, Nienke E; Siemensma, Elbrich P C; Tummers-de Lind van Wijngaarden, Roderick F A; Donze, Stephany H; Festen, Dederieke A M; van Alfen-van der Velden, Janielle A E M; Stijnen, Theo; Hokken-Koelega, Anita C S (The journal of clinical endocrinology and metabolism, 2016)
Patients with Prader-Willi syndrome (PWS) are severely at risk to develop morbid obesity, diabetes mellitus type 2, and cardiovascular disease, leading to high mortality. They have an increased fat mass (FM) and decreased lean body mass (LBM). During childhood, GH treatment counteracts the natural course of increasing obesity. Discontinuation of GH treatment at attainment of adult height (AH) might deteriorate their improved clinical condition, whereas continuation might benefit them. To investigate the effects of GH versus placebo on body composition in young adults with PWS who were GH treated for many years during childhood and had attained AH. Two-year, randomized, double-blind, placebo-controlled crossover study with stratification for gender and body mass index in 27 young adults with PWS. PWS Reference Center in The Netherlands. Crossover intervention with GH (0.67 mg/m · d) and placebo, both during 1 year. Body composition, measured by dual-energy x-ray absorptiometry. During placebo, FM increased (relative change +21.5%; P < .001). Compared with placebo, GH treatment resulted in lower FM (-2.9 kg; P = .004) and higher LBM (+1.5 kg; P = .005), representing relative changes of -17.3% FM and +3.5% LBM. Both limb and trunk FM percentage were lower during GH versus placebo (relative change +17.3% and +15.6%; P < .001 and P = .007, respectively). No GH-related adverse events occurred. GH-treated young adults with PWS who have attained AH benefit from continuation of GH treatment. FM increases during placebo, whereas GH versus placebo results in lower FM and higher LBM. Thus, GH treatment maintains the improved body composition without safety concerns.